Planning and positioning mHealth interventions in developing countries. Issue 2 (June 2019) - Eze, Emmanuel; Gleasure, Rob; Heavin, Ciara
Highlights: The planning and positioning differentiates between interventions at two levels. First, we differentiate between interventions targeting traits and states, the latter being situation-specific, and former that seek to improve individual's abilities, job knowledge, and skills as they relate to an mHealth tool. Second, we differentiate between individual and social interventions, the former being resilient to personnel change, and the latter seeking to improve crucial situations that would otherwise cause social systems to break-down around an mHealth tool. This creates a simple 2 × 2 matrix to lay out the portfolio of interventions in an mHealth project. Abstract: Objective: The objective of this paper is to develop a framework for the planning and positioning of mHealth interventions in developing countries. Method: The description of the framework uses an illustrative case from Enugu State, Nigeria. Planning and positioning for this case involved a number of interventions including workshops, training sessions, and other attempts to socialise mHealth tools and canvass for local and regional support. Results: The planning and positioning differentiates between interventions at two levels. First, we differentiate between interventions targeting traits and states, the latter being situation-specific. Second, we differentiate between individual and social interventions, the latter being resilient to personnel change. This creates a simple 2 × 2 matrix to lay out the portfolio of interventions in an mHealth project. Conclusion: The framework offers support to governments, decision makers, and developers as they design an assemblage of mHealth interventions. This added clarity means the framework also helps to analyse 'as is' structures and behaviours. The framework further provides support for reflecting on projects, as interdependent goals in different quadrants can be assessed against specific interventions.